Comparative analysis of lumbar cerebrospinal fluid drainage versus lumbar puncture effectiveness in patients with aneurysmal subarachnoid hemorrhage - Jiahui Liu; Qiushi Chen; Kun Sun; Lianshu Ding (Scientific Reports)
Abstract Subarachnoid hemorrhage (SAH) from ruptured intracranial aneurysms causes significant morbidity and mortality. Although prophylactic lumbar cerebrospinal fluid (CSF) management is widely used, the relative benefits of continuous lumbar cerebrospinal fluid drainage compared to intermittent lumbar puncture remain undefined. This study compared clinical outcomes between these two approaches in patients with aneurysmal SAH. This single-center retrospective study included 222 patients with aneurysmal SAH treated between January 2023 and December 2023. Patients were assigned to continuous lumbar cerebrospinal fluid drainage (n = 103) or intermittent lumbar puncture (n = 119). The primary outcome was the modified Rankin Scale (mRS) score at 6 months, categorized as good (0–2) or poor (3–6). Secondary outcomes included secondary infarcts, intracranial infections, hydrocephalus, and mortality. At 6 months, the lumbar drainage group exhibited significantly better outcomes (79% vs. 58%, relative risk [RR] 1.36, 95% CI [0.70, 0.85], p = 0.002) and lower rates of intracranial infection (0% vs. 11%, p = 0.002) and hydrocephalus (6.8% vs. 23.5%, RR 0.29, 95% CI [0.03, 0.13], p = 0.001) compared to the lumbar puncture group. Secondary infarcts occurred in 17.4% of the lumbar drainage group versus 28% of the lumbar puncture group (RR 0.63, 95% CI [0.11, 0.26], p = 0.099). No significant difference in mortality was observed between the groups (5.8% vs. 7.5%, RR 0.79, 95% CI [-1.35, 0.79], p = 0.608). Continuous lumbar cerebrospinal fluid drainage was associated with improved clinical outcomes, fewer intracranial infections, and reduced hydrocephalus incidence compared to intermittent lumbar puncture in patients with aneurysmal SAH. These findings advocate for the early adoption of continuous lumbar cerebrospinal fluid drainage in clinical practice.